1994
DOI: 10.1111/j.1399-3054.1994.tb00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Protochlorophyll(ide) forms in hypocotyls of dark‐grown bean (Phaseolus vulgaris)

Abstract: The protochlorophyll(ide) forms and plastid ultrastructure were investigated in hypocotyls of dark‐grown seedlings of kidney bean (Phaseolus vulgaris L. cv. Brede zonder draad). By deconvolution of the fluorescence emission spectra into Gaussian components three protochlorophyll(ide) forms were found with maxima at 633, 642 and 657 nm, respectively. The ratio of protochlorophyll(ide) emitting at 657 nm to protochlorophyll(ide) emitting at 633 nm decreased downwards the hypocotyl. The gradient was established a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…The spectra of the 4‐day‐old hypocotyls (Fig. ) were very similar to those of the etiolated hypocotyls (McEwen et al ). The result of the Gaussian resolution showed somewhat different components: instead of the 642 nm band (McEwen et al ), we found a component at 644 nm that is common in etiolated leaves (Böddi et al ) and small, 0.5 nm differences in the positions of the 631 and 656 nm components.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…The spectra of the 4‐day‐old hypocotyls (Fig. ) were very similar to those of the etiolated hypocotyls (McEwen et al ). The result of the Gaussian resolution showed somewhat different components: instead of the 642 nm band (McEwen et al ), we found a component at 644 nm that is common in etiolated leaves (Böddi et al ) and small, 0.5 nm differences in the positions of the 631 and 656 nm components.…”
Section: Discussionsupporting
confidence: 71%
“…) and plastid ultrastructure (Fig. ) to those developed in artificial darkness (McEwen et al ). A similar phenomenon was observed in soil‐shaded pea epicotyls (Vitányi et al ).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations